Improving surgical antibiotic prophylaxis adherence and reducing hospital readmissions: a bundle of interventions including health information technologies. Issue 4 (26th November 2018) - Ribed, Almudena; Monje, Beatriz; García-González, Xandra; Sanchez-Somolinos, Mar; Sanz-Ruiz, Pablo; Rodríguez-González, Carmen Guadalupe; Sanjurjo-Saez, María
Abstract : Objectives: Infection following orthopaedic surgery is a feared complication and an indicator of the quality of the hospital. Surgical antibiotic prophylaxis (SAP) guidelines are not always properly followed. Our aim was to describe and evaluate the impact of a multidisciplinary intervention on antibiotic prophylaxis adherence to hospital guidelines and 30-day postoperative outcomes. Methods: The study was carried out from January to May 2016 and consisted of creating a multidisciplinary team, updating institutional guidelines and embedding the recommendations in the computerised physician order entry system which is linked to dose and renal function alerts, educational activities and pharmaceutical bedside care of patients in the orthopaedic department. A prospective pre–post study was carried out in accordance with the Declaration of Helsinki. The following information was recorded: patient and surgery characteristics, adherence to SAP guidelines, surgical site infections, length of hospital stay and rate of readmission 30 days after discharge. Statistical analyses were performed using SPSS 18.0. Results: Eighty three orthopaedic patients of mean±SD age 68.2±17.0 years (44.6% male, 40 in the pre-intervention group and 43 in the intervention group) were included. Cefazolin was the recommended and most commonly administered antibiotic agent. In the intervention group, an improvement in global adherence to guidelines was achieved (76.7% vs 89.9%; p=0.039): antibiotic duration (75.0% vs 97.7%), correct dosage post-surgery (55.0% vs 76.7%), timing of administration (57.5% vs 72.1%), antibiotic pre-surgery prescription (92.5% vs 97.7%). Three surgical site infections were detected in the pre-intervention group and none in the intervention group (p>0.05). Length of hospital stay was reduced by 1 day and readmission decreased by 15% (p=0.038). Conclusions: SAP is used in daily practice in most orthopaedic patients. The implementation of a multidisciplinary programme based on health technology improved the adherence to guidelines and appeared to reduce the readmission rate.